Preliminary Findings into Current State of Breeding Population of Golden Eagle in Armenia - Levon A. Harutyunyan; Lusine A. Aghadjanyan (Пернатые хищники и их охрана)
In the 1990’s, in the South Caucasus, at least 75–100 breeding pairs were known, nevertheless, there is no exact data on Golden Eagles in Armenia. Various estimations were done for the species in the early 2000’s, varying between 20–80 breeding pairs. According to the Red Book of Animals of RA, published in 2010, the population of the Golden eagle consists of 34–38 breeding pairs. Additionally, during our recent sporadic field studies of raptor species we did not observe nesting activities in many previously known Golden Eagle breeding territories. Hence, in order to understand the status and to clarify all the uncertainties, in 2023 we began targeted research on the Golden eagle breeding population in the Republic of Armenia.